The last days of Lilah Goodluck [large type] - Scott, Kylie (Center Point Large Print, 2024)
"'Be quiet and listen: He is cheating on you. You will be passed over for the promotion. The winning numbers are 5-8-12-24-39-43. The name of your soulmate is Alistair George Arthur Lennox. And I'm very sorry to tell you this, but you will die next Sunday.' When Lilah Goodluck saves the life of Good Witch Willow as they're crossing a busy L.A. street, the last thing she expects is five unwanted predictions as a reward. Who gives someone the winning lotto numbers then tells them they've only got a week to live? And who believes in that nonsense anyway? But when the first three predictions come true within twenty-four hours, Lilah's disbelief turns to mild panic. She's further horrified when she nearly runs a car off the road that belongs to Alistair Lennox, who just happens to be the illegitimate son of the British king. While Alistair is intrigued by her preposterous story, Lilah is adamant about resisting the heat between her and the playboy prince. If she denies he's her soulmate, then the last prediction can't come true, right? As the days count down, they become maybe friends . . . and then maybe more. But between the relentless paparazzi and some disapproving royals, finding time for love isn't easy, especially when her days may be numbered."--